68Ga DOTATATE PET/CT of Non–FDG-Avid Pulmonary Metastatic Hemangiopericytoma. (October 2016) - Hung, Te-Jui; Macdonald, William; Muir, Tracey; Celliers, Liesl; Al-Ogaili, Zeyad
Abstract : Abstract: We present the FDG and 68 Ga DOTATATE PET/CT findings of a 68-year-old woman with pulmonary metastases 28 years after her initial diagnosis of central nervous system hemangiopericytoma. The largest of the pulmonary lesions showed prominent 68 Ga DOTATATE uptake with comparatively minimal FDG avidity. Hemangiopericytoma is a rare mesenchymal tumor that arises from malignant pericytes, cells that form the walls of capillaries and postcapillary venules. This case demonstrates the potential of radiolabeled somatostatin analogs as a therapeutic option in the setting of widespread metastatic disease.